2015
DOI: 10.1089/jpm.2014.0384
|View full text |Cite
|
Sign up to set email alerts
|

Facility-Related Factors Influencing the Place of Death and Home Care Rates for End-Stage Cancer Patients

Abstract: These results suggest that it may be possible to increase the rate of home care for end-stage cancer patients and meet their desires regarding the place of death through approaches to establish trust-based relationships with them and their families, such as strengthening manpower in home-visit nursing agencies and promoting collaboration between visiting nurses and family physicians in charge during home visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 9 publications
0
9
0
12
Order By: Relevance
“…Satisfaction in care quality represents trust in the healthcare provider, which is associated with better mental and functional outcomes for the care recipients. 26,27 This trust is earned by family members and staff through compassion and responsiveness, but eroded by incompetent care, lack of communication and cooperation, or lack of concern for family or staff. 26,28,29 Thus, a crisis is like a "magic mirror revealing goblins," differentiating between a "good" and a "bad" facility as per family members' perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction in care quality represents trust in the healthcare provider, which is associated with better mental and functional outcomes for the care recipients. 26,27 This trust is earned by family members and staff through compassion and responsiveness, but eroded by incompetent care, lack of communication and cooperation, or lack of concern for family or staff. 26,28,29 Thus, a crisis is like a "magic mirror revealing goblins," differentiating between a "good" and a "bad" facility as per family members' perceptions.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Previously, the authors conducted preliminary studies to confirm its usefulness, especially for palliative home care. 17 , 18 Interestingly, in this study, this tool was found to be useful for the continuation of home care. As demonstrated in previous studies, 4 , 19 home care is not more disadvantageous to end-stage cancer patients in their last days than hospital treatment, but factors explaining this have yet to be clarified.…”
Section: Discussionmentioning
confidence: 60%
“…[9242829] There were also situations where the decision-making did not proceed due to <Difficulty for the patient to talk about the disease conditions and death with medical professionals>[9101516] as illustrated by the reports that it is difficult for patients to ask medical professionals about medical matters,[1016] and that medical professionals make the ideas of patients on death ambiguous. [915] Further, as [Social resources available], <Characteristics of community>,[20252732] <Nursing care services at home>,[92128293334] <Medical professionals patients can consult with>,[113536] and <Support from the family>[910172427282937] were extracted.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, we selected 20 articles from among the identified articles by excluding 334 articles that had no descriptions about the decision-making about a place of death, six articles that focused on childhood cancer patients and their parents, three articles focusing on noncancer patients, and one article focusing on cancer patients with developmental disorders, 27 case study reports, and nine articles addressed at only medical professionals. Adding ten articles from a manual search using commonly known literature and cited articles to the twenty, we reviewed thirty articles[789101115161718192021222324252627282930313233343536373839] in total.…”
Section: Methodsmentioning
confidence: 99%